PERLINDUNGAN HAK CIPTA SEBAGAI JAMINAN KREDIT BANK BERDASARKAN HUKUM POSITIF INDONESIA - SAMIUDDIN SAMIUDDIN; Eka Jaya Subadi (Private Law, 2023)
The purpose of this study is to determine the regulation of copyright as an object of bank credit guarantees based on positive law in Indonesia, and copyright protection as an object of bank credit guarantees based on positive law in Indonesia. The research method in this thesis is normative legal research methods. The conclusion is a). The economic rights of copyright can be the object of debt guarantees because of the nature of copyright as an intangible movable object so that it can be guaranteed with fiduciary as regulated in Article 17 Indonesia Copyrights Act. So that the Creative Economy Law was issued and implemented regulations to realize copyright as object guarantees through an intellectual property-based financing mechanism. b). Copyright protection consists of two types, namely preventive and repressive protection. Preventive protection is carried out through a copyright and fiduciary registration mechanism at government institutions, while repressive protection is through civil or criminal justice mechanisms or Alternative Financial Services Sector Dispute Resolution Institutions.